RGB Three-Channel SWE-Based Ultrasomics Model: Improving the Efficiency in Differentiating Focal Liver Lesions - Cheng, Mei-Qing; Xian, Meng-Fei; Tian, Wen-Shuo; Li, Ming-De; Hu, Hang-Tong; Li, Wei; Zhang, Jian-Chao; Huang, Yang; Xie, Xiao-Yan; Lu, Ming-De; Kuang, Ming; Wang, Wei; et al. (Frontiers in Oncology, 2021)
Objective: To explore a new method for color image analysis of ultrasomics and investigate the efficiency in differentiating focal liver lesions (FLLs) by Red, Green, and Blue (RGB) three-channel SWE-based ultrasomics model. Methods: 130 FLLs were randomly divided into training set (n = 65) and validation set (n = 65). The RGB three-channel and direct conversion methods were applied to the same color SWE images. Ultrasomics features were extracted from the preprocessing images establishing two feature data sets. The least absolute shrinkage and selection operator (LASSO) logistic regression model was applied for feature selection and model construction. Two models, named RGB model (based on RGB three-channel conversion) and Direct model (based on direct conversion) were used to differentiating FLLs. The diagnosis performance of the two models was evaluated by area under the curve (AUC), calibration curves, decision curves, and net reclassification index (NRI). Results: In the validation cohort, the AUC of the RGB model and Direct model in characterization on FLLs were 0.813 and 0.926, respectively (p = 0.038). Calibration curves and decision curves indicated that the RGB model had better calibration efficiency and provided greater clinical benefits. NRI revealed that the RGB model correctly reclassified 7% of malignant cases and 25% of benign cases compared to the Direct model (p = 0.01). Conclusion: The RGB model generated by RGB three-channel method yielded better diagnostic efficiency than Direct model established by direct conversion method. The RGB three-channel method may be promising on ultrasomics analysis of color images in clinical application.